Contenção com parede de jet grout autoportante em maciço arenoso: análise pelo método dos elementos finitos - Manuel Pereira (2010)
Using a computer program based on the finite element method, the behaviour of an excavationin a sandy soil supported by a jet grout wall is analysed. The constitutive behaviour of the soil issimulated by the p-q-0 critical state model. Special emphasis is given to the analysis of thestresses (horizontal, vertical and shear stresses), stress levels and displacements of the soil, aswell as the stresses, displacements and earth pressures on the wall.